Impact of Teaching Cohesive Devices to Iranian EFL learners: Case of IELTS writing task 2 examination - Marashi, Syed Mojtaba (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2020)
The notion of “textuality” encouraged Halliday and Hasan in 1976 to present their model of discourse analysis through raising questions about whether “cohesion” was a semantic concept or a structural relation, whether a text was a structural unit or not or even if there were semantic or structural relationships within a text. Cohesion was like the glue that unified the meaning within a text through binding the textual elements. Tackling relations of meaning and references in a text was often related to cohesion. A text can be cohesive if its units were bound together with explicit or implicit relations. Cohesion was often defined as the network of lexical, grammatical, and other relations which provide links between various parts of a text. The units of a cohesive text were not just a random set of sentences. Writing section on IELTS was commonly considered one of the most difficult parts of test. The test takers cannot even understand what to do with the tasks provided. They eventually wrote without knowing the expected direction. Therefore, there should be a fast way to equip students well to successfully cope with such hindrances. This research was an action research report of 10 students to make them better understand and answer writing tasks on IELTS test by employing probing techniques as one of test taking strategies. As the result, teaching material about cohesive devices, according to criteria and references to IELTS writing task 2, could help students to understand of their logic on writing proper materials.